Safety Data Sheets as a Hazard Communication Tool: An Assessment of Suitability and Readability - Kevin Ho; Thomas Tenkate (Elsevier, 2024)
Background: Safety data sheets (SDSs) are hazard communication materials that accompany chemicals/hazardous products in the workplace. Many SDSs contain dense, technical text, which places considerable comprehension demands on workers, especially those with lower literacy skills. The goal of this study was to assess SDSs for readability, comprehensibility, and suitability (i.e., fit to the target audience). Methods: The Suitability Assessment of Materials (SAM) tool assessed SDSs for suitability and readability. We then amended the SAM tool to further assess SDSs for comprehensibility factors. Both the original and amended SAM tool were used to score 45 randomly selected SDSs for content, literacy demand, graphics, and layout/typography. Results: SDSs performed poorly in terms of readability, suitability, and comprehensibility. The mean readability scores were Flesch-Kincaid Grade Level (9.6), Gunning Fog index (11.0), Coleman-Liau index (13.7), and Simple Measure of Gobbledygook index (10.7), all above the recommended reading level. The original SAM graded SDSs as "not suitable" for suitability and readability. When the amended SAM was used, the mean total SAM score increased, but the SDSs were still considered "not suitable" when adding comprehensibility considerations. The amended SAM tool better identified content-related issues specific to SDSs that make it difficult for a reader to understand the material. Conclusions: In terms of readability, comprehensibility, and suitability, SDSs perform poorly in their primary role as a hazard communication tool, therefore, putting workers at risk. The amended SAM tool could be used when writing SDSs to ensure that the information is more easily understandable for all audiences.